Kualitas Pelayanan Publik - Fitrianingsih, Sela; Mozin, Sri Yulianty; Nani, Yacob Noho (Jambura Journal of Administration and Public Service, 2024)
This research aims to determine and analyze the quality of public services at the SAMSAT office, Bonepantai District, Bone Bolango Regency. The approach used is qualitative with descriptive research type. Data collection uses interviews, observation and documentation. Data analysis uses the Miles and Huberman model. This research shows that the quality of public services at the SAMSAT office in Bonepantai District, Bone Bolango Regency has been implemented well with various commitments to improve service aspects that need to be optimized. The service looks professional and structured in terms of direct evidence (Tangible). In terms of reliability, there is routine monitoring and evaluation to ensure services meet standards. Its responsiveness stands out with efficient queue management and willingness to respond to requests quickly. Service assurance is reflected through transaction security and a focus on the interests of the community. The aspect of empathy (Empathy) is also maintained by friendly treatment, attention and a helpful attitude towards the community. Overall, this office provides responsive, reliable, safe and empathetic service to the community.